2006
DOI: 10.1002/cyto.a.20287
|View full text |Cite
|
Sign up to set email alerts
|

Individual cell‐based models of the spatial‐temporal organization of multicellular systems—Achievements and limitations

Abstract: Computational approaches of multicellular assemblies have reached a stage where they may contribute to unveil the processes that underlie the organization of tissues and multicellular aggregates. In this article, we briefly review and present some new results on a number of 3D lattice free individual cell-based mathematical models of epithelial cell populations. The models we consider here are parameterized by bio-physical and cell-biological quantities on the level of an individual cell. Eventually, they aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 67 publications
0
56
0
1
Order By: Relevance
“…22,26,25 Drasdo and Höhme 22 compare the growth of MCTSs and tumor monolayers using a model based on spherical cells for which the interactions between cells and between cells and substrate are modeled by interaction potentials, and the motion and growth of cells is simulated using a Metropolis algorithm. From the results of their numerical simulations they suggest that the shift from exponential to linear growth in monolayers with access to abundant nutrient can be attributed to cell-cell contact-mediated growth inhibition; cells in the interior of the monolayer are sufficiently compressed that their growth is inhibited.…”
Section: Off-lattice Single-cell Modelsmentioning
confidence: 99%
“…22,26,25 Drasdo and Höhme 22 compare the growth of MCTSs and tumor monolayers using a model based on spherical cells for which the interactions between cells and between cells and substrate are modeled by interaction potentials, and the motion and growth of cells is simulated using a Metropolis algorithm. From the results of their numerical simulations they suggest that the shift from exponential to linear growth in monolayers with access to abundant nutrient can be attributed to cell-cell contact-mediated growth inhibition; cells in the interior of the monolayer are sufficiently compressed that their growth is inhibited.…”
Section: Off-lattice Single-cell Modelsmentioning
confidence: 99%
“…For example, Drasdo and Hoehme [82] have shown that contact inhibition due to mechanical stress can explain the equal expansion speed at significantly different glucose medium concentrations in growing multicellular spheroids of EMT6/Ro cells. The same mechanism could explain different growth speeds in expanding one-cell thick dense monolayers observed by Bru et al [90], and growth saturation of multicellular spheroids in agarose gel [62,82,144] observed by Helmlinger et al [11], and Galle et al [153]. Recently Delarue et al [154] confirmed inhibition of proliferation in tumor spheroids by compressive stress.…”
Section: Achievements Limitations and Practical Usementioning
confidence: 72%
“…New approaches started to emerge and developed with a huge technical progress in computer abilities: agent based models or individual based models or multi-agent models [248], [268], [63], [65], [135], [109]. Consisting of a mix of deterministic equations and stochasticity and a lot of computer programming, these new models were aimed at describing either a cell motion, its interactions with the inner and outer cellular environment, or interactions of a group of cells in the bone marrow.…”
Section: The 2000's: From One Generation To Anothermentioning
confidence: 99%